Cartas ao Max: limiar afetivo da obra de Max Martins - Lima, Élida (2012)
Through experiments with writing, love letters and other writings the author appropriates the voice of the poet Max Martins to think about topics such as poetry, knowledge, memory, language and subjectivity. The work invents poetic devices to operate with the poems, becoming itself a device of subjectivity. The text turns out to discuss some questions of literary criticism by proposing a critical intensity. A selection of poems by Max Martins also serves as an poetic-loving introduction to the author: it is a book within the book, a double reading, a contaminated reading. Letters to Max operates at threshold in between the language and the one who speaks. This is a work of writing